A NOTE ON SELECTION EFFECTS OF THE HAND RULE. (25th August 2011) - Baumann, Florian; Friehe, Tim
ABSTRACT: The famous Hand rule weighs the burden of precaution against the reduction in expected harm. The burden may be type‐specific, implying different standards of care for different injurer types. We show that this fact may be exploited by principals in their search for minimized individual costs. Principals may hire agents with high cost of care‐taking although other agents are available. This is shown in a unilateral‐care setting either with perfect or with asymmetric information. We therefore highlight a neglected downside of the negligence rule.